Unravelling mystery: renal tubular acidosis in a teen with Southeast Asian Ovalocytosis – a case report - Mohd Mussadik, Umul Khairil Fatimah; Zaki, Hafizatul Solehah; Hasim, Husna Syaza; Hamdan, Asmah Hanim; Chng, Kay Ly (Malaysian Society of Pathologists, 2025)
Introduction: Hypokalaemia paralysis is a rare but fatal condition caused by severe potassium depletion, leading to muscle weakness and potential respiratory failure. Renal tubular acidosis (RTA), which has been associated with Southeast Asian Ovalocytosis (SAO), exacerbates potassium loss, increasing the risk of severe electrolyte imbalances and hypokalaemia. We present a forensic case of a 15-year-old girl with no known medical history, who experienced progressive weight loss and weakness but did not seek further medical attention. A week before her death, she developed bilateral lower limb paralysis and loss of appetite before being found deceased at home. Case Report: Autopsy revealed a cachexic, pale individual with poor hygiene and no external injuries. Internally, both lungs showed pulmonary infarctions, the kidneys appeared pale, and the heart was grossly unremarkable. Histopathology, confirmed with special stains, revealed pulmonary infarction with antemortem microthrombi, renal changes consistent with RTA, and cardiomyocyte wasting. A full blood picture indicated mild anaemia of inflammation with underlying SAO. Additionally, nucleated red blood cells suggesting a hypoxic response. Postmortem potassium levels remained low at 3.9 mmol/L. The cause of death was determined as hypokalaemia paralysis, with RTA and underlying SAO as contributing factors. Conclusion: This case underscores the fatal risk of chronic hypokalaemia in SAO patients with renal dysfunction. The link between SAO and RTA highlights the need for early recognition, electrolyte monitoring, and timely intervention. Forensic pathology plays a key role in uncovering overlooked metabolic disorders, emphasising the importance of a multidisciplinary approach and greater awareness to prevent avoidable deaths.